Relationship Between Prior Knowledge and Creative Thinking Ability in Chemistry - Dewi Satria Ahmar; Ramlawaty; Melati Masri; Ansari Saleh Ahmar (Educational Process: International Journal, 2017)
This study aims to determine the relationship between prior knowledge and creative thinking ability of 11th Grade science students. This research is ex post facto. The population for this research was 11th Grade science students at a public school in Takalar, Indonesia, and consisted of 39 classes with a total enrollment of 1,537 students. In selecting the sample, the study employed stratified purposive random sampling technique in order to select 134 of the 11th Grade science students (from SMAN 1 Takalar, SMAN 3 Takalar, SMAN 1 Polongbangkeng Selatan, and SMAN 3 Polongbangkeng Utara). The data was collected by using a prior knowledge test that consisted of 16 items (α = 0.883) and a verbal creativity test consisting of 18 items (α = 0.808). Data were analyzed using correlation and regression analysis. The coefficient correlation between the two variables is 0.619 with p = 0.000 (p <0.05). This value indicates the existence of a relationship between prior knowledge and creative thinking ability in chemistry students and that there is a positive relationship between the two variables.